Amber in the Iron Age communities of the Kuyavia region. A case study of Gąski site no. 18 - Suchowska-Ducke, Paulina; Danielewska-Teska, Milena; Bednarczyk, Józef; Stolpiak, Barbara; Talarczyk-Andrałojć, Małgorzata (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
The historic region of Kuyavia has long represented an important area of cross-cultural communication in the heart of the Polish lands. During the Iron Age, Kuyavia evolved into a transit area for the amber trade between continental Europe and the Mediterranean region. This had transformative effects on the area’s inhabitants, known as members of the Przeworsk Culture, for instance in Gąski site no. 18, where the remains of a Pre-Roman Iron Age cemetery and a later settlement have been preserved. The small amounts of amber recovered from the burials suggest an initially marginal importance of amber in the material culture. This stands in stark contrast to the site’s later development when its inhabitants realized the commercial significance of amber and the advantages of their location, and were actively involved in the exchange of the fossilized resin. Amber artefacts were produced in specialized workshops where nu- merous objects have been found among imports, such as glassware, Roman coins, and terra sigillata.